2014
DOI: 10.1016/j.rbmo.2014.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Impact of high serum progesterone during the late follicular phase on IVF outcome

Abstract: With ovarian stimulation for IVF, serum progesterone concentration may increase during the last few days of stimulation. Several factors, mainly the intensity of the ovarian response to gonadotrophins, have been identified to explain progesterone elevation but many other issues remain uncertain. The aim of this narrative, nonsystematic review is to address the nonconsensual issues of the reasons and consequences of premature progesterone elevation during ovarian stimulation. The determination of the optimal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 60 publications
(83 reference statements)
0
20
0
4
Order By: Relevance
“…The finding of elevated progesterone levels, a known trigger of premature ovulation (18,75), in patients with a type 3 EnP suggests that an early opening of the window of implantation leads to its premature closure, preventing successful embryo implantation. While the findings from this study may be limited due to clinician-to-clinician variability in grading EnP, the association between elevated serum progesterone and a hyperechogenic endometrium with associated decreased endometrial receptivity has been widely reported (7678) in ETs performed without aneuploidy screening.…”
Section: Discussionmentioning
confidence: 90%
“…The finding of elevated progesterone levels, a known trigger of premature ovulation (18,75), in patients with a type 3 EnP suggests that an early opening of the window of implantation leads to its premature closure, preventing successful embryo implantation. While the findings from this study may be limited due to clinician-to-clinician variability in grading EnP, the association between elevated serum progesterone and a hyperechogenic endometrium with associated decreased endometrial receptivity has been widely reported (7678) in ETs performed without aneuploidy screening.…”
Section: Discussionmentioning
confidence: 90%
“…14,15 KOS sırasında gerçekleşen prematür LH yük-selmesi ise literatürde foliküler fazda LH seviyesinin 10 mIU/mL veya üstüne çıkması olarak tanım-lanmış ve LH yükselmesinin gebelik sonuçları üze-rine etkisini araştıran çalışmalarda mevcuttur. 6 Esnek (flexible) antagonist protokolle IVF uygulamalarını inceleyen üç çalışmada, prematür LH yük-selmesi düşük gebelik oranlarıyla ilişkilendiril-miştir, ancak hiçbirinde preovülatuar dönemde P düzeyleri ölçülmemiştir.…”
Section: Discussionunclassified
“…17 Ayrıca, bu alanda yapılan diğer iki çalışmada da yine tüp bebek sikluslarında prematür P yükselmesinin özellikle endometriyal reseptiviteyi bozarak gebelik sonuçlarını negatif yönde etkileyeceği öne sürülmüştür. 18,19 Geç foliküler fazda prematür P yükselmesini tetikleyen temel faktörler arasında kullanılan gonadotropinin dozu, serum hCG günü estradiol dü-zeyi ve elde edilen oosit sayısı daha önceki tüp bebek sikluslarında prematür P yükselmesinin gö-rülmesi sayılabilmektedir. 7,9,14,20,21 hCG günü foli- kül sayısının prematür P yükselmesi üzerine etkisini araştıran, Kyrou ve ark.nın 207 tüp bebek antagonist siklusunda yaptığı bir çalışmada, hCG günü P seviyesi >1,5 ng/mL olan hastalarda hCG günü ≥11 mm folikül sayısının anlamlı olarak yüksek olduğu ortaya konmuştur.…”
Section: Alıcı Işlem Karakteristikleri Eğrisiunclassified